Integrated Reporting and IFRS 3: an empirical study to Cost of Equity through Firm Risk and Investor Protection - Pavlopoulos, Athanasios; Iatridis, George Emmanuel (International Conference on Business and Economics - Hellenic Open University, 2023)
This study examines the relation of cost of equity associated with the disclosure quality of IFRS 3 and the Integrated Reporting (IR) compliance. Employing an IR sample composed of 498 non-financial firms that use IR either mandatorily or voluntarily from 2011 to 2019, we investigate the impact of IR and IFRS 3 disclosure quality on the cost of equity. Based on Breuer et al. (2018) and Chava (2014) we suggest two distinct channels through which IR and IFRS 3 can influence the cost of equity: firm risk and investor base. In companies with strong legal, cultural, and political factors, our results show that the cost of equity falls when a firm invests in IR and at the same time provides high levels of IFRS 3 information. Moreover, we find that higher IFRS 3 disclosure score lowers firms’ risk in companies with high IR compliance. We interpret the negative relation at higher levels of disclosure as evidence that investors consider firms with low levels of IR informativeness to be riskier. Finally, we find that the negative impact of IFRS 3 disclosure quality and of IR compliance to cost of equity is more intense when firms’ risk is low. JEL Classification: C 33; G17; G32; L2; M14. Keywords: integrated reporting, IFRS 3, accounting disclosure quality, cost of equity, firm risk and investor protection